Adolescents' Affective and Physiological Regulation Shape Negative Behavior During Challenging Equine Assisted Learning Activities - Pendry, Patricia; Carr, Alexa M.; Vandagriff, Jaymie L. (Frontiers in Veterinary Science, 2018)
This study examined associations between adolescents’ (N = 59; M age = 11.63) diurnal and momentary activity of the Hypothalamic Pituitary Adrenal (HPA) axis as marked by salivary cortisol, and affective and behavioral responses to their first, mounted equine assisted learning (EAL) activity. The introduction to riding occurred during the fifth week of an 11-week EAL program for at-risk and typically developing adolescents. Before the 11-week study began, participants collected 6 salivary cortisol samples at prescribed times (wakeup, 4pm, bedtime) over 2 days, from which indices of diurnal cortisol activity were derived. Six weekly sessions later, on the day of their first mounted activity, participants provided 3 salivary cortisol samples, reflecting their basal cortisol level at the end of their regular school day, and their cortisol levels linked to the beginning and end of their first ride. Participants reported on positive and negative emotion immediately before mounting the horse, and immediately after dismounting, using an 11-item survey. Using a 43-item checklist, three independent observers rated participants’ behavior throughout the 90-minute session. Regression analyses showed that adolescents with higher cortisol levels immediately before mounting reported higher levels of negative emotion (B = .350, p = .041) and lower levels of positive emotion (B = -.697, p = .013), while basal levels and potential dysregulation of cortisol diurnal patterns were controlled. Greater cortisol reactivity in response to 10 minutes of riding was linked to higher negative (B= 2.95, p = .001), and lower positive emotion (B = -3.73, p = .007) after dismounting. Higher levels of pre-ride negative emotion (B = 5.50, p = .046), and lower levels of post-ride positive emotion (B = -5.17, p = .027), and an increase in cortisol reactivity in response to riding (B = .242, p = .049), predicted higher levels of negative behavior during the 90-minute session that day. These findings show that participants’ HPA axis activity informs their program experience and behaviour. Results suggest that EAL facilitators need to employ strategies to down regulate adolescents’ physiological and affective arousal during mounted sessions to prevent and redirect negative behavior.